(untitled) (Jurnal Manajemen dan Ekonomi (JME), 2023)
The Kerobokan Traditional Village develops Kertih Bali economic activities based on the teachings of Tri Hita Karana aiming to improve and restore the economy of the Traditional Village after the Covid-19 Pandemic. The business sectors developed include the agricultural and plantation sectors, industry, education and tourism by utilizing village potential and based on local wisdom. Bali’s economic implications. Able to increase harmony in the aspects of Parahyangan, Pawongan and Palemahan.